Bacterial and yeast flora of root surface caries in elderly, ethnic Chinese - Shen, S; Samaranayake, LP; Yip, HK; Dyson, JE (Oral diseases, 2002)
OBJECTIVES: Root caries is emerging as a significant problem in the middle aged and elderly. As little data is available on the microbiology of root caries in Chinese cohorts, we evaluated 30 such lesions in elderly, institutionalized, ethnic Chinese. METHODS: Samples of carious dentine were aseptically taken from root caries lesions of 18 subjects (five males and 13 females, mean age 79.67 ± 8.57). The cultivable bacteria, both aerobic and anaerobic, were isolated and identified using standard methods and commercial identification kits. The yeasts were isolated on Sabouraud's agar and identified using the API system. RESULTS: The main findings were: (1) of the total isolates, 91.09% were Gram‐positive and 8.91% were Gram‐negative microorganisms; (2) the proportions of cocci and rods were 36.68 and 63.31%, respectively; (3) the predominant groups of organisms isolated were Streptococcus spp., Lactobacillus spp., Staphylococcus spp. and Actinomyces spp. with isolation frequencies of 100, 90.00, 73.33 and 63.33%, respectively; (4) the isolation frequency of yeasts belonging to Candida spp. (63.33%) was notably high although the proportion of yeasts within each sample was low (0.01%). Candida dubliniensis, a newly identified yeast species particularly prevalent in HIV infection, comprised 14.29% of yeasts. CONCLUSIONS: This study provides baseline information on the microbiologic features of root caries in the elderly, ethnic Chinese. Whilst our data on the most predominant bacteria isolated in root caries concur with those from other regions of the world the isolation of C. dubliniensis from these lesions has not been documented before.